2021
DOI: 10.1111/jcmm.16746
|View full text |Cite
|
Sign up to set email alerts
|

Alginate oligosaccharide alleviates D‐galactose‐induced cardiac ageing via regulating myocardial mitochondria function and integrity in mice

Abstract: Ageing is a crucial risk factor for the development of age‐related cardiovascular diseases. Therefore, the molecular mechanisms of ageing and novel anti‐ageing interventions need to be deeply studied. Alginate oligosaccharide (AOS) possesses high pharmacological activities and beneficial effects. Our study was undertaken to investigate whether AOS could be used as an anti‐ageing drug to alleviate cardiac ageing. D‐galactose (D‐gal)‐induced C57BL/6J ageing mice were established by subcutaneous injection of D‐ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…Numerous animal models have been developed for the study of hypoxia, of which the most widely used is the CIH model, which simulates the intermittent hypoxia that occurs in OSAHS [ 18 , 19 ]. Heart damage, the HW/BW ratio, or levels of BNP and ANP have been reported to be significantly increased in CIH animals or OSA patients [ 9 , 20 ]. Our experimental results are consistent with this research data and showed that silencing MR-1 could reduce the indices of CIH-induced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal models have been developed for the study of hypoxia, of which the most widely used is the CIH model, which simulates the intermittent hypoxia that occurs in OSAHS [ 18 , 19 ]. Heart damage, the HW/BW ratio, or levels of BNP and ANP have been reported to be significantly increased in CIH animals or OSA patients [ 9 , 20 ]. Our experimental results are consistent with this research data and showed that silencing MR-1 could reduce the indices of CIH-induced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…D-galactose- (D-gal-) induced aging animal model has been widely applied to study the senescence mechanism and antiaging efficacy of drugs [ 15 ]. It is considered as an agent for inducing animal senescence for its ability to accumulate ROS, which further brings about a physiological state similar to aging, consisting of decreased antioxidant activity, increased free radical level, and enhanced oxidative stress level in all organs of the organism [ 16 , 17 ]. Pogostemon cablin is a Chinese herbal medicine with the functions of dispelling dampness and removing heat and external syndrome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the underlying mechanisms of Nob for the prevention of D-gal-induced C2C12 cell aging, we examined the signaling pathway involved in autophagy-dependent catabolism. AMPK-activated kinase (AMPK) has a vital role in the regulation of autophagy [ 28 , 29 ]. Therefore, we evaluated the expression of phosphorylated AMPK at Thr172 (p-AMPK) and AMPK in CK and D-gal-induced C2C12 myoblasts treated with DMSO or Nob.…”
Section: Resultsmentioning
confidence: 99%